THU0061 Patients' Perceptions of Risk, Risk Communication and Predictive Testing for Rheumatoid Arthritis. (15th July 2016) - Falahee, M.; Simons, G.; Stack, R.J.; Raza, K.
Abstract : Background: Early treatment of rheumatoid arthritis (RA) is associated with improved clinical outcomes. There is a growing research interest in the identification of biomarkers to predict the development of RA in order to facilitate early treatment and preventive interventions. First degree relatives of individuals with a diagnosis of RA are at an increased risk of developing RA and are therefore likely candidates for predictive/preventive approaches. However access to this group is currently dependent on the cooperation of existing RA patients. Objectives: To understand patients' perceptions of risk and predictive testing for RA, and their likelihood of communicating with their relatives about the risk of developing RA in the future. Methods: Twenty-one RA patients (15 females and 6 males; aged 35 – 80 years) took part in semi-structured interviews. The interviews explored perceptions of risk of RA, family communication about risk, predictive testing, and risk reduction strategies. Interviews were audio-recorded, transcribed verbatim and analysed using thematic analysis. Results: Many patients were aware of genetic risk factors for RA and identified one or more relatives who they felt were at risk of developing RA in the future. Some patients described feelings of responsibility or guilt for their relatives' increased risk of developing RA. Environmental risk factors such as infection and psychosocial stress were also suggested, though few patients mentioned that smoking is associated with an elevated risk of RA. Patients described a lack of public awareness about RA and the causes of RA. They also referred to a lack of understanding, by their relatives as well as by the general public, of the negative impact that this condition has on their quality of life. Many patients held positive views of predictive testing for RA and were of the opinion that prediction would typically be associated with timely and positive preventive intervention. Those with negative views attributed these to their uncertainty about the accuracy of predictive tests, the availability of approaches (including therapeutic ones) to reduce RA risk and the potential for risk knowledge to cause unnecessary worry. Patients generally expressed willingness to communicate with their relatives about their risk of RA. However many patients identified relatives that they were not in contact with, or communicated with infrequently. Some mentioned that they would not pass on information to particular relatives who they did not get on with. Patients referred to choosing which relatives to communicate with, and described likely variation amongst relatives in their receptivity to risk information, and their likelihood of acting on such information. Reasons suggested for this included relatives being too busy, being in denial of their susceptibility, preferring to deal with things when they happen, being likely to worry, and feeling that RA is not serious enough to warrant action. Conclusions: Accurate information about risk factors for RA, and the potential impact of RA on quality of life, is needed to support family communication about RA risk. Strategies for the management of RA that target relatives of existing patients need to take into account that communication of risk information via patients is likely to be restricted and/or selective. Disclosure of Interest: None declared